2007
DOI: 10.1089/ten.2006.0302
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated Endogenous Repair: Making Tissue Engineering Simple, Practical, and Economical

Abstract: Facilitated endogenous repair is a novel approach to tissue engineering that avoids the ex vivo culture of autologous cells and the need for manufactured scaffolds, while minimizing the number and invasiveness of associated clinical procedures. The strategy relies on harnessing the intrinsic regenerative potential of endogenous tissues using molecular stimuli, such as gene transfer, to initiate reparative processes in situ. In the simplest example, direct percutaneous injection of an osteogenic vector is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 33 publications
1
96
0
1
Order By: Relevance
“…25,46,47,116 Some strategies for stimulating isolated stem cells include the use of inductive and conductive signaling molecules, either in purified form (e.g., BMP-2) 114,115 or from extracted endogenous tissue and fluids (e.g., PRP). 117 Kitamura et al 117 showed histological and mechanical evidence that BMSCs loaded with PRP regenerated bone in a dog mandible defect model comparable to autologous bone controls.…”
Section: Incorporating Scbts Into the Designmentioning
confidence: 99%
“…25,46,47,116 Some strategies for stimulating isolated stem cells include the use of inductive and conductive signaling molecules, either in purified form (e.g., BMP-2) 114,115 or from extracted endogenous tissue and fluids (e.g., PRP). 117 Kitamura et al 117 showed histological and mechanical evidence that BMSCs loaded with PRP regenerated bone in a dog mandible defect model comparable to autologous bone controls.…”
Section: Incorporating Scbts Into the Designmentioning
confidence: 99%
“…Since bone formation and bony repair occur rapidly within the growth plate injury site (starting after 1 week following the injury), there is the possibility that the long length of time it takes for MSC harvest, in vitro expansion and implantation could limit the usefulness of this in vitro MSC expansion/transplantation cell-based therapy for growth plate regeneration initially after growth plate injuries. Ultimately, potential mobilisation and use of a patient's own endogenous MSCs to regenerate the growth plate injury site immediately following injury would be ideal with the development of an in situ endogenous progenitor cell therapy, which can potentially circumvent all these limitations of the in vitro MSC approach (De Bari et al 2003, Evans et al 2007) as well as the need for the surgical removal of the formed bony repair tissue later on. However, more work in future on this area is needed to identify the most optimal signals and support to mobilise sufficient amounts of endogenous MSCs into the growth plate injury site and promote their expansion and cartilage regeneration at the growth plate injury site.…”
Section: Potential In Situ Approach For Growth Plate Regeneration Mobmentioning
confidence: 99%
“…In contrast to more complex approaches in tissue engineering, we advocate the use of simpler methods that harness the intrinsic regenerative potential of endogenous tissues, using biological stimuli to initiate and promote natural healing in situ. This concept has been termed facilitated endogenous repair by Evans et al 46 and the ultimate goal is to enable clinicians to use tissue engineering that is not only successful but also cheap, safe and clinically expeditious. The proposed method is a single-step procedure that can be easily implemented in standard clinical settings, avoids the usual drawbacks associated with gene therapy because it is administered locally, and excludes the expensive in vitro production of autologous and engineered tissues.…”
Section: Presence Of Adenoviral Vector In the Surrounding Synovial LImentioning
confidence: 99%